160k views
0 votes
The equation of a circle is x^2+y^2-2x +6y-6=0. Find the center and radius of the circle by completing the square.you must include all steps. Your response must be at least 5-7 sentences at a minimum.

User Owe
by
4.7k points

1 Answer

0 votes

Answer:

The center of the circle is at;


(1,-3)

The radius of the circle is;


r=4

Step-by-step explanation:

Given the equation of circle;


x^2+y^2-2x+6y-6=0

we want to re-write it in the form;


(x-h)^2+(y-k)^2=r^2

where;


\begin{gathered} (h,k)\text{ is the center of the circle} \\ r\text{ is the radius} \end{gathered}

Applying Completing the square method;


\begin{gathered} x^2+y^2-2x+6y-6=0 \\ x^2-2x+1+y^2+6y+9=6+1+9 \\ (x-1)^2+(y+3)^2=16 \\ (x-1)^2+(y+3)^2=4^2 \end{gathered}

comparing the derived equation to the general form we have;


\begin{gathered} h=1 \\ k=-3 \\ r=4 \end{gathered}

Therefore;

The center of the circle is at;


(1,-3)

The radius of the circle is;


r=4

User Nahuel
by
5.0k points